Click-iT trinucleotide cap analog: Synthesis, mRNA translation, and detection. (1st January 2023) - Senthilvelan, Annamalai; Vonderfecht, Tyson; Shanmugasundaram, Muthian; Potter, Jason; Kore, Anilkumar R.
Graphical abstract: Abstract: The first example of the synthesis of a new trinucleotide cap analog containing propargyl group such as m 7, 3′- O -propargyl G(5′)PPP(5′)Am pG is reported. The effect of the propargyl group in trinucleotide analog with a standard trinucleotide cap analog (GAG), m 7 G(5′)ppp(5′)Am pG was evaluated with respect to their capping efficiency, in vitro T7 RNA polymerase transcription efficiency, and translation activity using cultured A549 lung carcinoma epithelial cells. The new propargyl cap analog is a substrate for T7 RNA polymerase. Notably, the mRNA capped with the propargyl cap is translated ∼ 1.3 times more efficiently than the mRNA capped with the GAG cap. The most characteristic feature of the new propargyl cap analog is that the presence of the propargyl group allows further modification of the mRNA by chemical ligation of an azide-containing fluorescent-labeled substrate to the mRNA via click chemistry.